Overhead Lines - Papailiou, Konstantin O.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This handbook offers all aspects of Overhead Transmission Lines as the backbone of networks of electrical power. The content of the book includes, after a historical flash-back: Planning and management concepts, electrical and mechanical considerations, influences of the weather, and on the environment, detailed design of all line components, construction and maintenance aspects, line optimization, and asset management, as well as a comparison between overhead lines and underground cables. The book was written by more than 50 experts and assembled through the Cigré study committee on Overhead Lines. This guarantees valuable exchange and dissemination of unbiased information for technical but also non-technical audiences. .
Introduction -- History of Overhead Lines in Cigre -- Planning and Management Concepts -- Electrical Design -- Structural and Mechanical Design -- Environmental Issues -- Overhead Lines and Weather -- Conductors -- Fittings -- Conductor Motions -- Insulators -- Supports -- Foundations -- Overall Design -- Construction -- Maintenance -- Asset Management -- Uprating and Upgrading -- Overhead Lines and Underground Cables. .
Keywords: Electric power production; Transportation engineering; Traffic engineering; Building materials; Mechanics, Applied; Solids; Electrical Power Engineering; Mechanical Power Engineering; Transportation Technology and Traffic Engineering; Structural Materials; Solid Mechanics